Metallophthalocyanines for PDT Applications: A DFT Study - Aydogdu, Seyda; Hatipoglu, Arzu; Erdogmus, Ali (WORLD SCIENTIFIC PUBL CO PTE LTD, 2022)
Phthalocyanines (Pcs) are an important group of substances with interesting chemical and physical properties with many different application areas. The use of Pc compounds in photodynamic therapy (PDT), especially in the treatment of cancer, has gained great importance in recent years. In this study, the spectral and electronic properties of new PDT active anticancer non-peripheral tetrakis [2-mercaptoquinoline]phthalocyanine and metal complexes were examined by using Density Functional Theory (DFT). Their properties were computed in DMSO and water phases. The UV absorption spectrum study results show that the main transition responsible for the Q band of the molecular spectrum is from pi to pi*. The presence of the heavier atom in the Pc cavity has the effect of enhancing the fluorescence quantum yield. In addition, photochemical singlet oxygen production of newly synthesized phthalocyanine and metal complexes was also investigated. The calculated spectral (UV, IR, NMR) and singlet oxygen yield results were compared with the experimental ones and they were in good agreement.
Keywords: Phthalocyanine; DFT; photodynamic therapy; DMSO; global descriptors; SPECTROSCOPIC PROPERTIES; PHTHALOCYANINES; SUBSTITUENTS; THERAPY; SPECTRA; Chemistry